Faktore wat die werkverrigting van rekenaargebaseerde inligtingstelsels beïnvloed - P. J.S. Bruwer (South African Journal of Business Management, 1983)
– Factors which influence computer-based information systems The design and implementation of computer-based information systems have for a long time (and in some organizations are still being) accepted as primarily technical activities. As a result of this attitude about technology, the fact that practically all computer-based systems exist within the context of an organization has been largely ignored. From the literature it has emerged that many computer-based information systems have failed, not necessarily as a result of poor technical quality, but because certain other important aspects, which determine the success or the failure of a computer-based system have been left out of account. As a result of a research project, it will be shown in this paper which factors are the most important in their contribution to the success of computer-based systems.
Keywords: 650